ACESSIBILIDADE E NEURODIVERSIDADE NO PROCESSO ELEITORAL:: INICIATIVAS DO TRE-CE VOLTADAS A PESSOAS COM TRANSTORNO DO ESPECTRO AUTISTA - Paula Loureiro, Paulo Victor; Loureiro, Maria de Fátima de Melo; Loureiro Neto, Francisco Monteiro; Menezes, Silvia Rochelle Soares (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2025)
Ensuring inclusion and accessibility to public services provided by institutions is essential to promoting the values of equality, democracy and social justice, especially in relation to electoral elections. In order to ensure the participation of all voters in elections and the exercise of the right to vote, the Electoral Justice established the Electoral Justice Accessibility Program, Resolution-TSE n. 23.381/2012, with the aim of equalizing the opportunity for access to services and empowering people with disabilities or reduced mobility to vote. However, despite the progress made with the program, access to the free exercise of the vote faces barriers, especially for quadriplegics. In addition to social inequalities and discrimination, they suffer from a lack of assistive technologies for their inclusion in the Electoral Justice system. We were therefore approached to provide this access based on our experience in other sectors, such as assistive technology for autistic people. Now the challenge is to use this technology for quadriplegic people so that they can have access to the electoral process, promoting their human emancipation in relation to these elections. In this sense, this research aims to demonstrate our work on assistive technology, highlighting the development of its potential; it is based on neurotechnology, which promotes the autonomy of quadriplegic people so that they can participate in voting in the electoral process. This action will be carried out by the Regional Electoral Court of Ceará (TRE-CE), at the invitation of our work, through its Information Technology Secretariat (STI). To achieve this, we used the methodology of action research with a qualitative approach, the result of which is the development, at the Regional Electoral Court of Ceará, of a prototype of assistive technology based on non-invasive neurotechnology that allows a quadriplegic person to vote by selecting the numbers corresponding to the candidates in the election by means of their brain waves, by blinking their eyes.